Peran Kelembagaan dalam Memberdayakan Usaha Kecil Masyarakat Asli Papua di Kabupaten Jayapura - Katjong, Kadir (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine, analyze and explain the role of banking institutions in empowering small businesses of Indigenous Papuans in Jayapura Regency and the role of KADIN and KAPP Papua in empowering small businesses of Indigenous Papuans in Jayapura Regency. The type of research used is empirical legal research because it is motivated by the idea that law cannot be separated from people's lives in the form of values and attitudes/behavior carried out, so that the study of law does not only involve normative aspects, but law can be studied from its empirical aspect, namely how the law is. in fact in people's lives. The results of the research reveal that after the implementation of special autonomy for the Papua Province, the empowerment of small businesses of the indigenous Papuan community has not been carried out optimally by the Provincial, Regency and Jayapura City Governments, so it is not in accordance with the application of the theory of justice which emphasizes that justice is fairness and should always be fought for through correlation. and improving social institutions, economic institutions and other institutions through agreements that are used as a legal basis to be directed towards justice for all interested parties. Likewise, the role of banking institutions is not yet optimal, because loans in the form of MSME credit and KUR are hampered by collateral problems. Specific forms of empowerment for small businesses have not yet been regulated, so the Regency/City Government needs to make a Regional Regulation (PERDA) regarding small businesses of the indigenous Papuan community so that they have access to sources of financing and guarantees in an effort to empower small businesses of the indigenous Papuan community.